Instruir, confortar y cuidar: enfermeras visitadoras y de hospitales en México, 1920-1950 - Claudia Agostoni (Nuevo mundo - Mundos Nuevos, 2019)
The consolidation and expansion of the public health programs in Mexico during the course of the first half of the twentieth century was possible due to the work of numerous women in the different branches of nursing: as visiting nurses, hospital nurses and nurse assistants. The following pages will examine the importance that the training of visiting nurses acquired during the 1920s and 1930s for the Department of Public Health and the Rockefeller Foundation; the work that they carried out in favour of maternal and child health, as well as their participation during the smallpox vaccination campaigns in both urban and rural settings from the 1920s to the 1940s. Also, the pre-eminence that the modernization and construction of hospitals had as of the 1940s will be addressed, with the purpose to underline that the enlargement of the hospital system, alongside the increasing specialization of nursing, did not alter the perceptions and appreciations regarding their work in the realm of the state-led public health campaigns.